PENGARUH VARIASI INFILL DAN SPEED PRINTING TERHADAP SIFAT MEKANIK ADDITIVE MANUFACTURING - Fernando Desfriandi Saragih; A. Sofwan FA; Yovan Witanto (UNIB Press, 2022)
Additive Manufacturing (AM) is a production process that does not remove or remove some of the material in the production process but adds material. The added material is extruded by means of Fused Deposition Modeling (FDM) technique. The way it works is to create a number of layers or layers one on top of the other. The software application used is Inventor to create 3D models in the form of STL files. Then the STL file is opened in the Ultimaker Cura (UC) application, to create a Numerical Code in G-Code which is used as a control on a 3D printing machine. The filler material used to produce molds is Polylatic Acid (PLA). PLA filament is very widely used in the manufacturing process, because this PLA can produce strong and very neat prints. The general print temperature of PLA is between 180oC to 220oC. The purpose of this test is to find out the steps for implementing the AM process and to analyze the mechanical properties of the AM product using the FDM technique. In this study, the printed material was based on ASTM D638 type IV. This research was conducted to determine the effect of variations in infill and printing speed on printed results, with a horizontal orientation of the printing angle of 0o. The infill variations are line infill and concentric infill with printing speeds of 50mm/s and 60mm/s. The research procedure is to make a 3D printing model, the manufacturing process, and the testing process. The results showed that the choice of infill and speed printing variations had an effect on the mechanical properties. The mechanical properties of printing products differ according to the mode and speed. The infill line mode provides greater mechanical strength than that produced in concentric infill. At a speed of 60 mm/s, the product strength of the infill line mode is 32.5 MPa greater than the 27 MPa strength of the printed product from the concentric infill mode.